HELP2JUANA: Laguna Portal for Violence against Women and Children (VAWC) with E-Reporting and Mapping System - Mortel, Zerah Jane M.; Balahadia, Francis F. (International Journal of Computing Sciences Research; Vol 2 No 4 (2018): Vol 2, No 4, 2019)
Purpose – The study aims to develop a portal helping victims in Violence against Women and Children (VAWC). This VAWC Portal, map the area where VAWC incident happen. The VAWC portal also have e-reporting feature that will help the Women and Children in reporting when they experience abuse. Method – The proponents used the Agile Methodology was adopted in the software development. It includes the following stages: Planning; Requirements; Analysis and Design; Testing; Evaluation; and Deployment Then, it also facilitated testing and evaluation, purposive sampling was used to select the respondents. Two sets of questionnaires were developed, one for the residents and another for the government official. Results – It revealed that Help2Juana has passed the users’ evaluation, receiving high scores on User Satisfaction and Attribute of Usability in which Help2Juana web portal can be a tool in the campaign to end violence against women and their children. Conclusion – The system meets its objective to provide tool for the VAWC campaign. The high viability of using the Help2Juana web portal scores t from the participating government agencies and the women’s community indicate their readiness to adopt and use the system in the said campaign. This positive attitude towards the project can make Help2Juana useful in getting insights for planning VAWC prevention programs and policies, by taking advantage of the empirical data that are provided by the statistical tools integrated into the system. Recommendations – It recommends that the LGU’s and the Women’s Community in Laguna consider employing the Help2Juana system in the near future, to test out its capabilities in facilitating and supporting anti-VAWC programs. Other features related to improving government procedures can be added in the process to improve the quality of response to VAWC incidents. Practical Implications – The Women and Children victim of abuses can easily seek help and report the VAWC incident without shame through the use of Help2Juana. The system can give assistance and awareness regarding to related abuses to women, children and government official especially to R.A. 9262.